2012
DOI: 10.1007/s10963-012-9055-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Wild Boar from Domestic Pigs in Prehistory: A Review of Approaches and Recent Results

Abstract: New methods permit archaeologists to distinguish between wild boar and domestic pigs with greater confidence than has been hitherto possible. Metrical methods are the most commonly used; these are reviewed. Assemblages containing a wider range of measurements (as measured by the coefficient of variation [V]) than is found in one population suggest that two populations of different-sized pigs were present, probably indicating separate wild and domestic populations with little or no interbreeding. These assembla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 65 publications
(66 reference statements)
1
78
0
Order By: Relevance
“…The survivorship of juvenile Sus at KHH is also lower than at earlier PPNB sites [24,75,85]. Still, diverse potential pig management strategies [103] are known to cause significant demographic variability in domestic populations, leading to equifinality in Sus demographic profiles. Hunting is also expected to produce higher proportions of juveniles than in other progenitor taxa since more young Sus are naturally available due to high rates of fecundity [104].…”
Section: Discussionmentioning
confidence: 99%
“…The survivorship of juvenile Sus at KHH is also lower than at earlier PPNB sites [24,75,85]. Still, diverse potential pig management strategies [103] are known to cause significant demographic variability in domestic populations, leading to equifinality in Sus demographic profiles. Hunting is also expected to produce higher proportions of juveniles than in other progenitor taxa since more young Sus are naturally available due to high rates of fecundity [104].…”
Section: Discussionmentioning
confidence: 99%
“…Sus bones comprised on average ~30% of Ertebølle game assemblages151617. Traditional biometrical analyses of Ertebølle pig skeletal remains indicated that these animals were mainly large-bodied, and therefore were probably wild boar4151617.…”
mentioning
confidence: 99%
“…The lengths of pig lower M 3 s from Houjiazhai were measured according to the criteria of von den Driesch (). The reduction of lower M 3 size is considered as an important indicator of pig domestication, which is frequently used in wild/domestic determination (Evin et al, ; Rowley‐Conwy, Albarella, & Dobney, ; Albarella, Davis, Detry, & Rowley‐Conwy, ). However, overlaps between the ranges of M 3 lengths of wild boars and domestic pigs influenced by varying factors (geography, temperature, vegetation, foraging habitats, etc.)…”
Section: Methodsmentioning
confidence: 99%